Gap of SRHR in Climate Change Policies: a Case Study in Jepara and Banyumas Regencies - Ahmad Badawi (Jurnal Perempuan, 2015)
Risks of women’s SRHR is increasing due to limited access to water and food in climate change policy. Women’s vulnerability is very high regarding the masculinity of climate-related policy—specifically the minimum representation and participation of women in decision-making. This problematical situation has mounted women’s burden with the changing pattern of climate since women are having difficulties in managing their livelihood. This study found that mainstreaming gender is not being implemented in climate-change related policy in Banyumas and Jepara. In many cases, women are being marginalized and the aims of development does not touch the SDG Post-2015.